Consulting in the public sector - Gunter, Helen (Henry Stewart Talks, 2016)
Advising and helping public sector professionals, Policy changes in education, Education professionals as consultants within and outside the system, Consultants in education reform, 4K's in knowledge production, Knowledgeable polity